On the functions of class H'p and interpolation problems - Kabaila, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Кабайла. Некоторые свойства функций класса H'p и задачи интерполированияV. Kabaila. Kai kurios H'p klasės funkcijų savybės ir interpoliaciniai uždaviniai